2011
DOI: 10.1103/physrevlett.106.216101
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability of Corrugated Epitaxial Graphene Grown on Re(0001)

Abstract: We report on a novel approach to determine the relationship between the corrugation and the thermal stability of epitaxial graphene grown on a strongly interacting substrate. According to our density functional theory calculations, the C single layer grown on Re(0001) is strongly corrugated, with a buckling of 1.6 Å, yielding a simulated C 1s core level spectrum which is in excellent agreement with the experimental one. We found that corrugation is closely knit with the thermal stability of the C network: C-C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
111
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(121 citation statements)
references
References 32 publications
9
111
1
Order By: Relevance
“…The intercalated noble metal atoms damp the G/Re moiré pattern as evidenced by low-energy electron diffraction measurements shown in Figure 1(h) and also affect the core states of both graphene and Re. Previous photoemission studies of graphene on Re 21 already reported that the C 1s peak (black full curve in Figure 2(a)) exhibits two main contributions centered at binding energies 285.05 and 284.45 eV. This splitting is a consequence of the strong buckling of the graphene film (about 1.6Å according to DFT calculations 21 ), as the large corrugation defines differently interacting regions of the moiré depending on the carbon positions relative to the substrate atoms.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The intercalated noble metal atoms damp the G/Re moiré pattern as evidenced by low-energy electron diffraction measurements shown in Figure 1(h) and also affect the core states of both graphene and Re. Previous photoemission studies of graphene on Re 21 already reported that the C 1s peak (black full curve in Figure 2(a)) exhibits two main contributions centered at binding energies 285.05 and 284.45 eV. This splitting is a consequence of the strong buckling of the graphene film (about 1.6Å according to DFT calculations 21 ), as the large corrugation defines differently interacting regions of the moiré depending on the carbon positions relative to the substrate atoms.…”
Section: Methodsmentioning
confidence: 99%
“…Previous photoemission studies of graphene on Re 21 already reported that the C 1s peak (black full curve in Figure 2(a)) exhibits two main contributions centered at binding energies 285.05 and 284.45 eV. This splitting is a consequence of the strong buckling of the graphene film (about 1.6Å according to DFT calculations 21 ), as the large corrugation defines differently interacting regions of the moiré depending on the carbon positions relative to the substrate atoms. This leads to distinct C 1s components in the photoemission spectra, with the strongest interacting areas displaying contributions on the higher binding energy side of the spectra.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Graphene ripples less than 1 nm high, for example, have been shown to cause spatial charge redistribution [3,4] and electron scattering [5], to enhance graphene's chemical reactivity [6,7], and affect its thermal stability [8,9]. Aiming for high-quality graphene electronics, the search for suitable substrates has increasingly focused on layered materials, like mica [10], hexagonal boron nitride (h-BN) [11], or MoS 2 [12].…”
Section: Introductionmentioning
confidence: 99%
“…The van der Waals interaction sticks the graphene sheet to both the superconducting substrate and islands causing a non-uniform strain. Also, recent advances in fabrication of graphene membrane have made a situation that the wavelength, the amplitude and the orientation of out-of-plane deformation of a graphene membrane can be controllably produced [53][54][55][56][57].…”
mentioning
confidence: 99%